(untitled) (Journal of actual problems of jurisprudence, 2025)
As part of the ongoing transformation in criminal justice policy and digitalization of public administration, the penitentiary system requires a review of approaches to correction of individuals convicted. This study investigates means and methods of correction in Kazakhstan with an eye towards traditional practices versus digital technologies as tools of correction - with the ultimate aim being identifying digitalization’s potential as a means to enhance effectiveness while humanizing criminal punishment. Scientific and practical importance of this work lies in its detailed examination of Kazakhstan’s current correctional system with reference to international experiences, employing comparative legal, doctrinal, critical-analytical, and interdisciplinary methodologies in its methodology. The findings reveal that Kazakhstan, despite lacking a comprehensive digitalization strategy for its penal correction system, has both resources and institutional prerequisites necessary for the implementation of electronic monitoring, digital profiling, online education programs and artificial intelligence tools in the near future. Furthermore, research highlights the need to protect human rights, maintain algorithmic transparency and individualize rehabilitation approaches accordingly. The study’s value lies in providing direction for modernization of penitentiary policy, adopting successful international practices and formulating recommendations for legal, institutional and technological reform of Kazakhstan’s penal correction system. Furthermore, its practical significance lies in potentially applying proposed measures toward creating a national digital transformation strategy for prisons. Keywords: penal correction system, correction of convicts, digitalization, electronic monitoring, resocialization.